Sosialisasi Bahaya Gangguan Makan pada Kehamilan untuk Ibu dan Janin (Inovasi Sosial : Jurnal Pengabdian Masyarakat, 2025)
Pregnancy is a physiological process that involves various physical and psychological changes in women. One common psychological issue that can arise is anxiety related to body image, which can significantly influence the eating behaviors of pregnant women. This psychological challenge may lead to eating disorders such as anorexia nervosa, binge eating disorder, and bulimia nervosa. The presence of eating disorders during pregnancy can have detrimental effects on maternal health, including nutritional deficiencies, fatigue, and an increased risk of complications during pregnancy, such as preterm birth and gestational diabetes. Additionally, these disorders can negatively impact the fetus, resulting in inadequate nutrient intake, low birth weight, and developmental delays. Therefore, maintaining a healthy, balanced diet, alongside psychological support, is crucial for pregnant women. Health education, along with professional counseling and guidance from healthcare providers, plays a vital role in preventing and managing eating disorders during pregnancy. Such efforts ultimately contribute to optimal health outcomes for both the mother and the developing fetus, ensuring the well-being of both in the long term.